Risk Factors Associated with Acute Sarcopenia in Patients Hospitalized with COVID-19 - D. M. S. Silva; T. A. Valadão; C. Caporosi; J. E. Aguilar-Nascimento; D. B. Dock-Nascimento (Journal of Nutrition and Metabolism, 2024)
Background. The COVID-19 pandemic is an extraordinary global emergency. The pandemic has changed profoundly people’s lifestyles. This resulted in reductions in physical activity and changes in dietary intakes that have the potential to accelerate sarcopenia. Objective. The aim of this study was to evaluate the risk factors associated with acute sarcopenia in patients hospitalized with COVID-19. Methods. This was a cross-sectional study conducted from January/2021 to March/2022 in a private hospital in Cuiabá/MT, central region of Brazil. The main variable was the prevalence of acute sarcopenia among adults hospitalized with COVID19. Patients were assessed for acute sarcopenia using the SARC-F ≥4 questionnaire (strength, assistance with walking, rise from a chair, climb stairs, and falls), grip strength (<20 kg (female) and <35 kg (male)), and calf circumference (<33 cm (female) and <34 cm (male)). Results. In all, 213 patients aged 57.4 ± 15.4 years, 63.8% male, were studied. Thirty-four (16.0%) patients were diagnosed with acute sarcopenia. Advanced age (older people) and the percentage of weight lost ≥3% before hospitalization were independent risk factors for acute sarcopenia in hospitalized patients with COVID-19. Conclusion. Acute sarcopenia was present in 16% of patients. Advanced age and percentage of weight lost ≥3% were independent risk factors for acute sarcopenia in patients hospitalized with COVID-19.